Extreme Translation Events of Atlantic Tropical Cyclones - Wei Zhang (Atmosphere, 2021)
Changes in the translational speed of tropical cyclones (e.g., sluggish tropical cyclones) are associated with extreme precipitation and flash flooding. However, it is still unclear regarding the spatial and temporal variability of extreme tropical cyclone translation events in the North Atlantic and underlying large-scale drivers. This work finds that the frequencies of extreme fast- and slow-translation events of Atlantic tropical cyclones exhibited a significant rising trend during 1980–2019. The extreme fast-translation events of Atlantic tropical cyclones are primarily located in the northern part of the North Atlantic, while the extreme slow-translation events are located more equatorward. There is a significant rising trend in the frequency of extreme slow-translation events over ocean with no trend over land. However, there is a significant rising trend in the frequency of extreme fast-translation events over ocean and over land. The extreme slow-translation events are associated with a strong high-pressure system in the continental United States (U.S.). By contrast, the extreme fast-translation events are related to a low-pressure system across most of the continental U.S. that leads to westerly steering flow that enhances tropical cyclone movement. This study suggests that it might be useful to separate tropical cyclone events into fast-moving and slow-moving groups when examining the translational speed of North Atlantic tropical cyclones, instead of examining regional or global mean translational speed.